Parents’ Involvement in Students’ Home English Literacy Practices with Divers Populations - Imroatul Mufidah; Pratiwi Retnaningdyah; Ali Mustofa (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Not only school, but home literacy practices are extremely important in developing language and literacy skills. Using a case study, this research presents the cases of 6 Senior high school students from diverse backgrounds which is chosen because of their wide range of socioeconomic status, single parenting or working parent, parental educational, also their performance in EFL Classroom. Thorough ORIM framework, it is shown that each parent engages to the students’ home literacy practices in different aspects although not all of form of home literacy practices categories fulfilled in engaging students’ home literacy practices. Five factors influenced their English literacy practices. Both internal and external factors are examined. It becomes evident that fostering a holistic approach to literacy development demands concerted action from multiple stakeholders. Encouraging Family Engagement is suggested. Schools suggested to create and sustain family engagement programs aimed at empowering parents and caregivers to actively participate in their children's literacy development